2015
DOI: 10.1038/nsmb.3053
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of microbial glycans by human intelectin-1

Abstract: The glycans displayed on mammalian cells can differ markedly from those on microbes. Such differences could, in principle, be read by carbohydrate-binding proteins, or lectins. We used glycan microarrays to show that human intelectin-1 (hIntL-1) does not bind known human glycan epitopes but interacts with multiple glycan epitopes found exclusively on microbes: β-linked d-galactofuranose (β-Galf), d-phospho-glycerol-modified glycans, heptoses, d-glycero-d-talo-oct-2-ulosonic acid (KO) and 3-deoxy-d-manno-oct–2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
245
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(253 citation statements)
references
References 69 publications
6
245
1
1
Order By: Relevance
“…Specifically, it has been suggested that hIntL-1 recognizes furanose carbohydrate residues, including galactofuranose (Galf) and ribose (5). Our studies of hIntl-1 indicate that it does not bind ribose, but it does interact with ␤-Galf residues (26) and is thus not a general furanose-binding lectin. Analysis using glycan microarrays revealed that hIntL-1 does not bind any of the tested human glycans but rather binds diverse microbial glycan epitopes.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…Specifically, it has been suggested that hIntL-1 recognizes furanose carbohydrate residues, including galactofuranose (Galf) and ribose (5). Our studies of hIntl-1 indicate that it does not bind ribose, but it does interact with ␤-Galf residues (26) and is thus not a general furanose-binding lectin. Analysis using glycan microarrays revealed that hIntL-1 does not bind any of the tested human glycans but rather binds diverse microbial glycan epitopes.…”
mentioning
confidence: 81%
“…None of these epitopes are present on human glycans. In accord with its glycan specificity, hIntL-1 binds microbial cell surfaces, supporting a role for hIntL-1 in the recognition of intact microbes (26). Given these recognition properties and the presence of intelectins in diverse species, an intriguing possibility is that the intelectins serve as microbial detectors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…selectively binds to pathogenic organisms, suggesting its functions in microbial surveillance (40). Experimental studies have shown that omentin secretion is induced in endothelial cells by IL6 (41), one of the major inflammatory cytokines in response to infection and tissue damage.…”
Section: Discussionmentioning
confidence: 99%